(3GdeYjGQ GdeYQH hGdLGeY GdeZQH Yf aJGhi YdeGA EaQjbjI hGdCfOdS hGdeZQHs - (3CHh GdYHGS CMeO Hf jMji Hf eMeO Hf YHO GdhGMO Hf Ydj GdhfTQjSj,J (B914 (3g` s
(3ChdgG (B:s
(3SFd CHh eMeO YHO GdfhQ Hf eMeO GdTQja GdYeQGfi Yf RfbI ZjQ fGaPI cGf jONd YdjgG GdehGVY hUGQJ GdehGVY cdgG dQLd hGMO eG YOG YQVI hGMOI ebGHdI dhLgg GdOGNd s
(3BNQgG (B:s
(3EdG jejf GdQO adG JLJeY eY ZjQgG Ydi eG PgHG Edjg GdTjN hMcGg Yf GdTjN CHj GdeWQa , hYf GdTjhN fLR gPG GdSaQ ef GdeYjGQ s
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ GdahGJM HGdCShO hHGdCMeQ GdSejcs
(3HgG fhGRd GdHfjGf hGdhOjYI hGdYGQjI hGdgHGJ hGdUObI hGdYJb s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B269s
Keywords: (3Gdabg GdESdGejs